Predictors of incipient dysfunction of all cardiac chambers after treatment of metastatic renal cell carcinoma by tyrosine kinase inhibitors. Issue 4 (15th February 2016) - Moustafa, Sherif; Ho, Thai H.; Shah, Parth; Murphy, Katie; Nelluri, Bhargava K.; Lee, Howard; Wilansky, Susan; Mookadam, Farouk
ABSTRACT: Purpose: We aimed to explore the hypothesis that early subclinical cardiac chamber dysfunction secondary to tyrosine kinase inhibitors (TKIs) in patients with metastatic renal cell carcinoma could be signaled by abnormal cardiac mechanics demonstrated by velocity vector imaging. Methods: Echocardiographic images were acquired from the apical views in 23 metastatic renal cell carcinoma patients. All patients had baseline and at least a 3‐month follow‐up echocardiogram after receiving TKI therapy. Subendocardial borders of all the cardiac chambers were traced to obtain volumetric and deformation indices. Results: Mean age was 67 ± 9 years with 92% men. The right ventricle peak systolic global longitudinal strain (GLɛ) and strain rate were significantly lower after TKIs (−23.49 ± 5.1 versus −19.81 ± 5.5, p = 0.002 and −1.52 ± 0.52 versus −1.24 ± 0.35 p = 0.02, respectively). LV GLɛ was not statistically different. Volumetric and deformation indices showed a minimal decrease of the right atrium reservoir and conduit functions, and no significant changes of left atrial function. Conclusions: The right heart exhibited greater strain changes than the left heart after TKI treatment. The implications of these findings and their potential significance warrant further work. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44 :221–230, 2016